2001
DOI: 10.1136/adc.85.5.421
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage activation syndrome: a potentially fatal complication of rheumatic disorders

Abstract: Conclusion-MAS is a rare and potentially fatal complication of childhood rheumatic disorders. Most of our patients were female, and most cases were preceded by infection. Bone marrow studies support the diagnosis. Deranged renal function may be a poor prognostic sign. Aggressive early therapy is essential. (Arch Dis Child 2001;85:421-426)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
329
3
28

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 414 publications
(369 citation statements)
references
References 29 publications
9
329
3
28
Order By: Relevance
“…Furthermore, 26% of patients with s-JIA in this study developed MAS. This was in line with recent reports [39,40] rather than with an older report [41].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, 26% of patients with s-JIA in this study developed MAS. This was in line with recent reports [39,40] rather than with an older report [41].…”
Section: Discussionsupporting
confidence: 93%
“…70 A similar benefit was reported for high dose steroids in nine children with MAS (seven with sJIA) in England. 3 More recently, glucocorticoids, along with other immunosuppressive therapy, were reported to be effective in 13 children with sJIA in China 71 and in 6 children with sJIA in India. 72 Hence, high dose steroids are routinely used to treat MAS as part of sJIA.…”
Section: Traditional Therapy For Mas In the Setting Of Sjiamentioning
confidence: 99%
“…21 Evidence suggests that MAS etiopathogenesis is associated with a hereditary defect in immunoregulation, predisposing sufferers to a histiocytic proliferation in response to specific triggering agents such as viruses, 15,22 autoimmune diseases, 6,[22][23][24][25][26][27][28] immunodeficiencies (such as during the accelerated phase of the Chédiak-Higashi syndrome) 3 and drugs. 7,10 In the majority of studies of JIA, the criteria for MAS diagnosis are not defined. Ravelli 4 performed a retrospective study of 88 patients with JIA (72 reported in published literature and 16 new Italian cases).…”
Section: Commentsmentioning
confidence: 99%
“…3,12 Macrophage activation syndrome can be triggered by viral infectious agents such as: varicella-zoster, 13 hepatitis A, 14 Epstein-Barr 8 and coxsackie B, 15 in addition to therapy with gold, acetylsalicylic acid and other nonsteroidal antiinflammatory drugs, 6,12 methrotrexate, 10 sulfasalazine and penicillamine. 7 The etiopathogenesis of MAS is unknown. The macrophage activation liberates proteases which activate plasminogen, leading to the formation of plasmin with fibrin degradation, triggering fibrinolysis and DIVC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation